Photocatalytic removal of N2O in cropped fields using R-Leaf - Carlos J. Bueno-Alejo; Yusuf K. Khambhati; Apostolos Papadopoulos (Applied Catalysis O: Open)
The removal of greenhouse gases (GHGs) is critical for combating climate change. Strategies focused solely on emission avoidance or reduction are insufficient to meet the urgency of the crisis. While there is numerous studies at the laboratory scale, few address the challenges in real-world field conditions and no previous studies have specifically targeted N₂O removal in agricultural fields. N₂O is the third largest contributor to the greenhouse effect but has the highest greenhouse potential, being 275 times more potent than CO₂. Since agriculture is the primary anthropogenic source of N₂O emissions, addressing its removal within this sector is of utmost importance. Photocatalysis, has been extensively studied as a promising solution to this issue. However, most of these studies are conducted under laboratory conditions, and many encounter challenges to deliver similar results when applied in open-field environments. This study presents the results of applying R-Leaf, a product developed by Crop Intellect Ltd., to agricultural crops for the removal of N₂O. A methodology is proposed to measure and estimate N₂O removal based in well-known micrometeorological methods allowing for quantification of photocatalyst performance in open field. Average N₂O concentrations were measured at two different heights in both treated and control fields (1 ppb difference on average), the vertical fluxes were calculated, and the N₂O removal achieved by R-Leaf equated to an average of 1.96 tons of CO₂ equivalent removed per hectare over a crop season. On the view of this results, this technology has the potential to transform agricultural fields into effective air-cleaning systems.